2020
DOI: 10.1371/journal.pone.0238652
|View full text |Cite
|
Sign up to set email alerts
|

Development of the parental self-efficacy scale for preventing challenging behaviors in children with autism spectrum disorder

Abstract: Background Almost all children with autism spectrum disorder (ASD) have experienced challenging behavior, including disruptive and aggressive behavior symptoms to both themselves and others. In conjunction with appropriate strategic parenting, challenging behavior can be prevented by empowering children's sociality and optimizing their environment. However, a means of measuring such parenting has yet to appear. This study developed the Parental Self-Efficacy Scale for Preventing Challenging Behaviors in Childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Moreover, 35.7% of caregivers had severe total burden preprogram that decreased post program to 0.0%. Table (7) denotes improving the mean changes of studied caregivers' self-efficacy post program compared by preprogram. Also, highly statistically significant variations concerning self-efficacy were found between pre and post implementation of the nursing intervention at P<0.001.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, 35.7% of caregivers had severe total burden preprogram that decreased post program to 0.0%. Table (7) denotes improving the mean changes of studied caregivers' self-efficacy post program compared by preprogram. Also, highly statistically significant variations concerning self-efficacy were found between pre and post implementation of the nursing intervention at P<0.001.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, Caregivers will develop, maintain, and improve social interaction opportunities for their children and enhance their growth and development. Additionally, improving caregivers ' self-efficacy to avoid challenging behavior will improve the mental health of both caregivers and children as well as prevent harm and maltreatment (7) . Caregivers have a great influence on the condition of their children with AD.…”
Section: Introductionmentioning
confidence: 99%
“…Another more recent instrument that can also be identified is the Parental Self-Efficacy Scale for Preventing Challenging Behaviors in Children with Autism Spectrum Disorder (PASEC), currently under development by Kabashima et al (2020). Like PSEMAS, PASEC also has as a limitation the focus on a specific domain of care and raising of children with ASD, the presence of challenging behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike Kabashima et al (2020) and Lu et al (2021), the study by Sofrnoff and Farbotko (2002) aimed to use an intervention program to promote the self-efficacy of parents of children with Asperger to cope with their child's challenging behavior. Thus, their research aimed to find ways to support the parents' self-efficacy in dealing with the challenging behavior of the child.…”
Section: Self-efficacy In Relation To the Childmentioning
confidence: 99%
“…In addition, parents who believed that IBI would have a positive effect on their child were also more likely to participate in the program themselves. Kabashima et al (2020) found that the Parental Self-Efficacy Scale for Preventing Challenging Behaviors in Children with Autism Spectrum Disorder (PASEC) can help prevent challenging behaviors in children, and thus promote parents' self-efficacy and contribute to improving the mental health of parents and children. When parents understood their children's feelings and behaviors, they were able to respond to them more appropriately.…”
Section: Knowledge and Skills Offered To Parentsmentioning
confidence: 99%